Application of benzo[a]phenoxazinium chlorides in antimicrobial photodynamic therapy of Candida albicans biofilms - Lopes, Marisa da Conceição Gomes (2014)
The use of Antimicrobial Photodynamic Therapy (APDT) as a new approach to treat localized Candida infections is an emerging and promising field nowadays. The aim of this study was to verify the efficacy of photodynamic therapy using two new benzo[a]phenoxazinium photosensitizers against Candida albicans biofilms: N-[5-(3-hydroxypropylamino)-10-methyl-9H-benzo[a]phenoxazin-9-ylidene]ethanaminium chloride (FSc) and N-(5-(11-hydroxyundecylamino)-10-methyl-9H-benzo[a]phenoxazin-9-ylidene)ethanaminium chloride (FSd). The photodynamic activity of dyes against C. albicans biofilms was evaluated by incubating biofilms with dyes in the range of 100-300 μM for 3 or 18 h followed by illumination at 12 or 36 J cm-2, using a xenon arc lamp (600 ± 2 nm). A total photoinactivation of C. albicans biofilm cells was achieved using 300 μM of FSc with18 h of incubation, followed by illumination at 36 J cm-2. Contrarily, FSd had insignificant effect on biofilms inactivation by APDT. The higher uptake of FSc than FSd dye by biofilms during the dark incubation may explain the greater photodynamic effectiveness achieved with FSc. The results obtained stresses out the FSc-mediated APDT potential use to treat C. albicans infections.